Enhancing Rural Tourism Development through IoT-Based Solar Internet Connectivity: A Case Study of Nanggelan Beach, Jember - Evio Tanti Nanita; Risse Rachmanita; Ansh Sharm; Keita Mahamadou Mandè (CV. Austronesia Akademika, 2026)
This study examines the implementation of an IoT-based off-grid solar internet system at Nanggelan Beach, Jember, Indonesia, as a green digital connectivity intervention designed to support sustainable rural tourism development. The objective of this research is to analyze how the integration of renewable energy, digital infrastructure, and community participation contributes to tourism promotion, local empowerment, and socio-economic opportunities in an underserved coastal destination. Employing a qualitative descriptive case study approach, the research used field observation, semi-structured interviews, evaluation forms, project documentation, and social media analysis to assess technological performance, community responses, and tourism promotion outcomes. The findings show that the solar-powered internet system provided relatively stable connectivity, supported continuous operation through renewable energy, and enabled local residents, particularly youth and small-scale tourism actors, to participate more actively in digital tourism promotion. Social media activity increased after the intervention, strengthening the online visibility of Nanggelan Beach and expanding opportunities for community-based destination branding. The study also found that digital literacy training and local involvement in system maintenance contributed to stronger community confidence, collective ownership, and emerging tourism-related economic opportunities. These results indicate that green digital connectivity can function not only as a technical infrastructure solution, but also as a socio-technical catalyst for inclusive and sustainable rural tourism transformation.